Disporum xilingense (Colchicaceae), a new species from Sichuan, China, and the exclusion of D. leucanthum from the Chinese flora - Zhu, Xin-Xin; Zhang, Chan; Shen, Bin; Liu, De-Tuan; Zhang, Lin (Phytotaxa, 2016)
Disporum xilingense is described from Sichuan, China. The new species is related to D. leucanthum and D. bodinieri, with which it shares similar terminal inflorescences, widely open and nodding flowers with tepals slightly saccate at the base. However, its narrowly lanceolate tepals 23–26 mm long with tapered lower part 5–6 mm long, stamens distinctly shorter than the tepals, and style equaling or slight longer than the tepals support recognition at the species rank. The new species is also similar to D. acuminatissimum in flower size and color, whereas D. xilingense differs by its acute apices of leaves and tepals, widely opening flowers, glabrous tepals only minutely papillate on the lower margin and inside, sharply narrowed and navicular tepal bases, stamens 14–16 mm long and style 24–26 mm long. Furthermore, data are reported to exclude D. leucanthum from the flora of China. The main morphological features of the new species are discussed and illustrations and an identification key are provided.